Marketing Strategy for Semar Rice in Increasing Sales - Prasetyo, Santo Febri; Soedjoko, Dodi Kusuma Hadi (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim : The aim of this research is to identify marketing strategies, internal and external environmental conditions and analyze the most effective strategies in increasing sales. This research uses qualitative research using researchers as an important tool for collecting and interpreting data. This data collection method includes documentation studies, interviews and direct observation. Design/Methode/Approach : The brand image of UD Sholeh Jaya Semar rice is well known and familiar to the public so that it does not raise public doubts about the quality of UD Sholeh Jaya's rice production to meet consumption needs. The marketing strategy for Semar UD Sholeh Jaya rice products is through direct distribution and indirect distribution. Where direct distribution is carried out with the marketed product being delivered directly to regular consumers or consumers (the general public) who immediately come to make purchases on the spot